2007
DOI: 10.1001/archpedi.161.12.1162
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization for Pneumonia in Young Children After Routine Pneumococcal Conjugate Vaccine Use in the United States

Abstract: In children younger than 2 years, the age group targeted for vaccination, pneumonia-related health care utilization in a privately insured population declined substantially following PCV7 introduction. These results suggest that PCV7 may play an important role in reducing the burden of pneumonia, resulting in major savings in medical care cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 29 publications
6
63
2
1
Order By: Relevance
“…Our findings are similar to the results of Grijalva et al [11], Zhou et al [12], and Durando et al [14]. It can be that, in an open population, as in our study, the effect of a PCV7 immunization program is greater than that seen in clinical trials because herd immunity can have an important role in the reduction of disease in both vaccinated and N-number of living individuals; n-number of pneumonia cases Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are similar to the results of Grijalva et al [11], Zhou et al [12], and Durando et al [14]. It can be that, in an open population, as in our study, the effect of a PCV7 immunization program is greater than that seen in clinical trials because herd immunity can have an important role in the reduction of disease in both vaccinated and N-number of living individuals; n-number of pneumonia cases Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The post-marketing study by Grijalva et al [11] revealed a 39% decrease in the all-cause pneumonia admission rate among children up to 2 years of age and a 65% decrease in the rate of pneumonia defined as pneumococcal. Zhou et al [12], comparing similar periods for children under 2 years of age, showed a 52% reduction of hospitalization and a 41.1% reduction of outpatient visits due to all-cause pneumonia and 57.6 and 46.9% for pneumococcal pneumonia, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies (4,8,10,11), in the present study, the number of patients hospitalized for pneumonia in the secondary medical facility declined after the beginning of official financial support of PCV vaccination. In particular, the number of patients with pneumonia other than confirmed viral or mycoplasmal pneumonia was markedly reduced.…”
Section: Discussionsupporting
confidence: 81%
“…Another study showed that as of April 2002 through March 2003, no cases of invasive V-serotype disease were seen in children Ͻ1 year of age, compared to 16 to 34 cases per year in the years before vaccine introduction, and similar reductions were seen in children Ͻ5 years of age (3). In a study of hospitalizations and ambulatory visits of families of 40 large United States employers due to all-cause and pneumococcal pneumonia from 1997 through 2004, Zhou and coworkers found that hospitalizations and ambulatory visits due to all-cause and pneumococcal pneumonia among children younger than 2 years declined significantly, with decreases of 41.1% to 57.6% (45). Projecting these data to the United States population, the total estimated direct medical expenditures for all-cause pneumonia-related hospitalizations and ambulatory visits of young children were reduced 45.3% (from an annual average of $688.2 million in 1997 to 1999 to $376.7 million in 2004).…”
Section: Vol 46 2008 Serotypes and Susceptibilities Of Invasive S mentioning
confidence: 76%